Another Race between Islam and Christianity: The Case of Flores, Southeast Indonesia, 1900-1920 - Steenbrink, Karel (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
Islam and Christianity arrived in the south-eastern islands of the Indonesian archipelago in two waves. The first wave started in about 1480 with the arrival of Arab and Indian (Gujerati) traders in the spice islands of the Northern Moluccas: particularly in Ternate and Tidore. They arrived through the island of Flores, and probably very quickly moved across to the island of Timor as well, to engage in trade in sandalwood, horses and slaves. In south-east Indonesia, as in most regions of the archipelago, the arrival of Islam occurred somewhat earlier than the coming of the first Christians. At that time, the two main centers of trade in south-east Indonesia, which also became centers for the new religions, were the islands of Solor and Ende.DOI: 10.15408/sdi.v9i1.674